PROPUESTA PARA INICIAR UN PROCESO DE CAMBIO ORGANIZACIONAL MODELO GAT - Bustamante Sánchez, Yolanda (2005)
The author proposes the G.A.T. Model so as to begin a change process in the organization and face the present time where the appropriate management of the human resources will be redundant on the promotion and benefit of the institutution.